Advances in nanoparticle-mediated cancer therapeutics: Current research and future perspectives - Deivayanai, V.C.; Thamarai, P.; Karishma, S.; Saravanan, A.; Yaashikaa, P.R.; Vickram, A.S.; Hemavathy, R.V.; Kumar, R Rohith; Rishikesavan, S.; Shruthi, S. (Cancer pathogenesis and therapy, 2025)
One in six deaths worldwide is caused by cancer, making it a major global health concern. Despite their effectiveness, traditional treatment approaches such as radiation therapy, chemotherapy, and surgery frequently have negative side effects and high costs. New approaches, such as gene therapy, are promising but are hampered by high costs and accessibility problems. Nanoparticles (NPs) facilitate targeted drug delivery by leveraging passive targeting mechanisms, such as the enhanced permeability and retention (EPR) effect, and by actively targeting surfaces with ligands for site-specific binding through the functionalization of surfaces. This approach enhances therapeutic results while lowering off-target toxicities. Notably, chemotherapeutic medications, immunotherapeutic agents, and photothermal therapies can now be delivered more precisely to the affected site using NP-based systems. By boosting particularity, reducing side effects, and tackling drug resistance, nanomedicine has the potential to revolutionize cancer treatment and ultimately advance personalized oncological care. These advancements highlight the possibilities for field growth, and future development regulations are detailed. [Display omitted] •Nanosized particles are explored for innovative and advanced cancer treatment methods.•Targeted drug delivery via active and passive targeting is highlighted.•Chemotherapy, immunotherapy, and photodynamic approaches are thoroughly explained.•Improvements in specificity and efficiency for targeted therapies have been discussed.•Biocompatibility and safety considerations are discussed for effective treatment.